Design and fabrication of vertical axis wind mill with solar system. (2020) - Vignesh, J.; Christopher, A. Simon; Albert, T.; Pravin Tamil Selvan, C.; Sunil, J.
Abstract: It is well known that the nonrenewable resources such as fossil fuels, oils, natural gas, etc. which will certainly get exhausted sooner or later. Among the various non-convention methods for generation of electric power, wind has found its place to be efficient. Taking into consideration the geographical attributes of our region, the vertical axis windmill will be efficient for power generation. The main objective of this paper is to design and fabricate a vertical axis wind mill that can be operated even at low wind speed.